Sound ideas - Krasny, Michael
Reading involves interpreting all types of texts: fiction, nonfiction, poetry, graphic novels, advertisements, spoken words, and more. Sound Ideas is a reader that acknowledges this and that a wide variety of linguistic backgrounds make up today's college classrooms. Sound Ideas addresses the needs and interests of this diverse audience, while maintaining strong connections to a history of ideas